The Structural and Magnetic Properties of FeII and CoII Complexes with 2-(furan-2-yl)-5-pyridin-2-yl-1,3,4-oxadiazole - Zoufalý, Pavel; Čižmár, Erik; Kuchár, Juraj; Herchel, Radovan (Molecules, 2020)
Two novel coordination compounds containing heterocyclic bidentate N,N-donor ligand 2-(furan-2-yl)-5-(pyridin-2-yl)-1,3,4-oxadiazole (fpo) were synthesized. A general formula for compounds originating from perchlorates of iron, cobalt, and fpo can be written as: [M(fpo)2(H2O)2](ClO4)2 (M = Fe(II) for (1) Co(II) for (2)). The characterization of compounds was performed by general physico-chemical methods-elemental analysis (EA), Fourier transform infrared spectroscopy (FT-IR), nuclear magnetic resonance (NMR) in case of organics, and single crystal X-ray diffraction (sXRD). Moreover, magneto-chemical properties were studied employing measurements in static field (DC) for 1 and X-band EPR (Electron paramagnetic resonance), direct current (DC), and alternating current (AC) magnetic measurements in case of 2. The analysis of DC magnetic properties revealed a high spin arrangement in 1, significant rhombicity for both complexes, and large magnetic anisotropy in 2 (D = -21.2 cm-1). Moreover, 2 showed field-induced slow relaxation of the magnetization (Ueff = 65.3 K). EPR spectroscopy and ab initio calculations (CASSCF/NEVPT2) confirmed the presence of easy axis anisotropy and the importance of the second coordination sphere.
Keywords: Iron; Models, Molecular; kobalt; Anisotropy; furany; Coordination Complexes; spektroskopie infračervená s Fourierovou transformací; elektronová paramagnetická rezonance; Spectroscopy, Mossbauer; spektroskopie Mossbauerova; Oxadiazoles; Magnetic Resonance Spectroscopy; oxadiazoly; Crystallography, X-Ray; Spectroscopy, Fourier Transform Infrared; Cobalt; železnaté sloučeniny; krystalografie rentgenová; molekulární modely; Ferrous Compounds; železo; magnetická rezonanční spektroskopie; Electron Spin Resonance Spectroscopy; Furans; anizotropie; komplexní sloučeniny